Effect of dietary manipulation on the microbial protein synthesis of sheep fed fish silage protein supplements - Barroga, Antonio J. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2007)
Two separate experiments were carried out to compare the microbial protein synthesis in sheep fed different fish silages as protein supplement. The fish silages were compared with the conventional protein supplements of fish meal and urea with sorghum silage (Experiment 1) and Italian ryegrass silage (Experiment 2) as basal rations with wheat bran and sweet potato as major sources of energy in the concentrate supplement. The raw materials of the fish silages consisted of the minced head (Experiment 1), the back frame and the viscera (Experiment 2) of yellow tail (Seriola quinqueradiata). In Experiment 1, the performance of sheep which had been fed the fish-silage-based diet was comparable with that of sheep given the urea-based protein supplement in terms of daily dry matter (DM) and organic matter (OM) intake but it was significantly lower than that of sheep fed the fish-meal-based protein supplement (p<0.05). However, in Experiment 2, after dietary manipulation of the fish-silage-based formulations, the performance of the sheep was already comparable with that of the sheep fed the urea-based and the fish-meal-based protein supplements. The nitrogen retention in sheep fed with the fish-silage-based diet in Experiment 2 was largely improved (0.21-0.41 g N kgW0.75), which is an indication of better N source and utilization, due to the significant increase in feed intake, resulting in higher N intake (0.96-1.57 g N kgW0.75). Accordingly, urinary allantoin excretion increased by two-fold (5.05 vs. 8.40 mmole -L). which was also observed in purine derivative excretion (6.65 vs. 11.90 mmole-L) and microbial protein synthesis, respectively (32.71 vs. 64.37 g d-1). Based on these findings, feed intake, nitrogen utilization and microbial protein synthesis in sheep can be largely improved by nutritional modification of fish silage mixed diets.